Thermal waste replacement as a sustainable approach to reinforced concrete beam design: A finite element study - Nur Farhayu, Ariffin; Nurul Natasha, Nasrudin; Aizat, Alias; Nor Hasanah, Abdul Shukor Lim; Abdul Muiz, Hasim; Muhammad Nor Syahrul, Zaimi (Bentham Open, 2024)
Introduction :The escalating global demand for infrastructure underscores the need for increased construction material use, particularly in concrete, a fundamental component of the construction sector. However, conventional aggregate extraction methods pose significant environmental challenges, including river pollution from sand extraction and deforestation due to rock quarrying. Repurposing industrial waste materials as sustainable concrete components is crucial to address the depletion of natural resources from sand and gravel use. In Malaysia, where electricity production relies on coal, power generation produces waste materials, specifically bottoms such as fly ash and coal combustion by-products in power plants. Disposing of this by-product, primarily in open landfills, raises significant environmental hazards for local communities, impacting health and safety. Aims: To address environmental concerns related to natural material depletion and by-product waste abundance, this study explores recycling coal bottom ash and fly ash from coal power plants as part of concrete materials in reinforced concrete beams. Additionally, the paper uses nonlinear analysis in ABAQUS software to explore the structural performance and behavior of RC beams incorporating high volumes of coal ash as replacements for fine and coarse aggregates. Methods: Six replacements spanning 50% to 100% were tested alongside 20% cement substitution with fly ash. The mixture includes a 50% replacement of natural fine aggregates with fine coal bottom ash and a 50% replacement of natural coarse aggregates with coarse coal bottom ash. The materials replacement calculation was based on the materials' volume due to the differences in density between the waste material and conventional materials. On the other hand, mechanical properties were assessed through four-point bending load tests, recording deflections, loads, and crack patterns. Finite element analysis models using ABAQUS were also performed to predict the beam behavior and validated against experimental responses. Besides, the parametric study with different beam lengths was also performed to observe the beam behavior and validate the input. Results: The inclusion of 100% coarse coal bottom ash (CCBA) and 100% fine coal bottom ash (FCBA) in the concrete mix resulted in significant enhancements in structural performance, surpassing the control RC beam with an ultimate load of 88 kN and a maximum deflection of 18.87 mm. The successful development of a finite element model using ABAQUS software for finite element analysis (FEA) showcases the capability of simulation tools in predicting structural behavior with differences within a 10% range. Besides, the parametric study revealed that longer beams exhibited more prominent cracks and severe failure, indicating the reliability of the input parameters in FEA. Conclusion: This study highlights the effectiveness of the proposed approach in enhancing RC beam performance. The findings validate the simulation tool's potential in predicting structural behavior and shed light on the complexities of concrete behavior under varying conditions. As future designs advance, these insights will inform more accurate and robust structural assessments, fostering innovation and improved engineering solutions.